2022
DOI: 10.1002/adfm.202211576
|View full text |Cite
|
Sign up to set email alerts
|

Inheritable Organic‐Inorganic Hybrid Interfaces with π–d Electron Coupling for Robust Electrocatalytic Hydrogen Evolution at High‐Current‐Densities

Abstract: Rational heterointerface engineering is crucial for superior and robust hydrogen evolution reaction (HER). Herein, a delicate organic-inorganic hybrid heterojunction based on the assembly of oxalate with polyaniline (PANI) for HER at high-current-densities is envisioned. Strong π-d electron coupling is achieved between the delocalized π electrons of PANI and the localized d electrons of oxalate metal sites. The CoC 2 O 4 nanosheets are grown on nickel foam (NF) with Ni 2+ ions substitution by the precursor etc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…For instance, Zhao et al designed the heterointerface between inorganic Co 0.59 Ni 0.41 C 2 O 4 and organic polyaniline (PANI) using the hydrothermal method and subsequent electrodeposition. 103 XPS and EXAFS analysis results confirmed the existence of π-d electron coupling at the heterointerface of the Co 0.59 Ni 0.41 C 2 O 4 @PANI composite. DFT calculations indicated that π-d electron coupling can unshift the d-band center of Co, enhance water adsorption and activation and optimize the H* binding energy, thus enhancing the HER activity.…”
Section: Design Strategies Of Electrocatalysts For High-current–densi...mentioning
confidence: 55%
See 1 more Smart Citation
“…For instance, Zhao et al designed the heterointerface between inorganic Co 0.59 Ni 0.41 C 2 O 4 and organic polyaniline (PANI) using the hydrothermal method and subsequent electrodeposition. 103 XPS and EXAFS analysis results confirmed the existence of π-d electron coupling at the heterointerface of the Co 0.59 Ni 0.41 C 2 O 4 @PANI composite. DFT calculations indicated that π-d electron coupling can unshift the d-band center of Co, enhance water adsorption and activation and optimize the H* binding energy, thus enhancing the HER activity.…”
Section: Design Strategies Of Electrocatalysts For High-current–densi...mentioning
confidence: 55%
“…(f) The surface reconstruction of electrocatalysts with the organic-inorganic heterointerface. 103 Copyright 2023, Wiley-VCH. cannot be overlooked for the practical application of the AEMWE.…”
Section: Anion Exchange Membrane Water Electrolysis (Aemwe)mentioning
confidence: 99%
“…[34,35] The electron paramagnetic resonance (EPR) spectra in Figure 2b [25,36] Oxygen vacancies in RuO 2 /Co 3 O 4 play important roles in surface synergistic heterocatalytic reactions, which adsorb activated reactant molecules and optimize the interface structure between metal and carrier, leading to the improvement of electrocatalytic performance in water splitting. [36][37][38] To gain a deeper insight into the electron transfer behavior between RuO 2 and Co 3 O 4 , an ultraviolet photoelectron spectrometer (UPS) test was performed to calculate the work function of pure Co 3 O 4 and RuO 2 /Co 3 O 4 (Figure 2c). [39] As shown in Figure 2c, the measured secondary electron cutoff energy (E cutoff ) of RuO 2 /Co 3 O 4 and Co 3 O 4 are 16.98 and 16.66 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Additional references cited within the Supporting Information. [36,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]…”
Section: Supporting Informationmentioning
confidence: 99%